Functional analysis of ESM1 by siRNA knockdown in primary and metastatic head and neck cancer cells. (30th October 2017) - Bender, Onur; Gunduz, Mehmet; Cigdem, Sadik; Hatipoglu, Omer Faruk; Acar, Muradiye; Kaya, Mesut; Grenman, Reidar; Gunduz, Esra; Ugur, Kadriye Serife
Abstract : Background: Genetic factors play a large role in cancer, and thus, there is a great desire to understand the effects of different genes in cancer and to also develop gene therapy for better treatments. Therefore, the development of alternative diagnosis and therapy modalities is of utmost importance. The aim of our study was to illuminate the role of ESM1 (endothelial cell‐specific molecule‐1, also known as Endocan) in proliferation and migration of head and neck cancer, thus helping to pave the way for new treatment modalities and predictive biomarkers. Methods: ESM1 expression was shown with immunofluorescence assay using confocal laser scanning microscope in primary and metastatic head and neck cancer cells. ESM1 expression was knocked down by RNA interference in head and neck cancer cells. Knockdown efficiency was evaluated by quantitative real‐time RT‐PCR and Western blot. Cell proliferation and migration assays were performed by xCELLigence real‐time cell analysis system. Results: Immunofluorescence assay showed nuclear localization and high expression of ESM1 in primary and metastatic head and neck cancer cells. ESM1 mRNA and protein levels were significantly decreased in ESM1‐knockdown cells compared to control. ESM1‐knockdown cells showed reduced proliferation and migration activity when compared to control cells. Conclusion: These findings suggest that ESM1 has roles on proliferation and migration of head and neck cancer cells.